Use of Optokinetic Chart Stimulation to Restore Muscle Strength and Function in a Severely Disabled Bed Bound Multi-Morbidity Patient with a Combination of Systemic Lupus Erythematosus, Critical Care Myopathy and Diabetic Neuropathy: A Case Study - Benjamin Chitambira (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2015)
Background and objective: Multiple morbidities in critical care myopathy tend to lead to poor outcomes. The objective of this case report is to describe the remarkable recovery of a bed bound critical care myopathy patient with lupus, phalangeal amputations and diabetic neuropathy. Methodology: An optokinetic chart was moved in front of the patient for 3 minutes laterally, then 3 minutes vertically and finally 3 minutes forwards and backwards. Sensory interaction for balance was added once patient could stand with assistance of one person. Results: For 54 days before commencement of optokinetic chart stimulation the patient was bed bound and being fed by a nasogastric tube. She had no trunk control. The aggregate manual muscle strength was 0/5 with best strength of 1/5 only in bilateral shoulder and hip muscle groups. After treatment the patient fed herself independently and was mobile with a wheeled zimmer walking aid and assistance of one person. Her aggregate strength improved to 5/5. The Barthel Index improved from 0/100 to 75/100. Conclusion: The multiple morbidities in this case report mitigated against natural recovery. Optokinetic chart stimulation needs further investigation as a multi-morbidity treatment in instances where severe deterioration of trunk control occurs.